Efeito da insulação scrotal sobre as características físicas e morfológicas do sêmen de touros jovens - Bonilla, Luciano; Santos, Aline Quadros; Borges, Juliana Correa [UNESP]; Siqueira, Jeanne Broch; Pinho, Rogério Oliveira; Gurzoni, Wanderlei Sevaybricher; Martins, Leonardo Franco; De Araújo Lima, Daniel Mendonça; Guimarães, Simone Eliza Facioni; Guimarães, José Domingos (My University, 2013)
The aim of this study was to evaluate the physical and morphological characteristics of semen from young cattle subjected to experimental testicular degeneration by scrotal insulation method. There were used three animals of the Holstein breed with an average of 12 months of age undergoing breeding soundness examination weekly for a period of 10 weeks. Semen was collected from animals by the method of electroejaculation and evaluated for physical characteristics of semen, sperm morphology and thermo-resistance test. Scrotal insulation for 120 hours increased scrotal temperature by 3.4 °C. The rectilinear progressive sperm motility and sperm vigor decreased between 7 to 28 days post-insulation (p>0.05) and sperm incidence with abnormal head increased between 21 to 35 days post-insulation. There was a decrease (p>0.05) in sperm motility during thermo-resistance test, for the periods post-insulation, indicating low sperm viability. The testicular degeneration induced by insulation bags may be temporary and even animals during puberty and adolescence have the ability for restructuring of the seminiferous epithelium and restoration of normal sperm production, although there is need for more recovery time.
Effect of scrotal insulation on physical and morphological semen features in young cattle
Keywords: Cattle; Scrotal insulation; Semen; Testicular degeneration